Population Ethics and Animal Farming - Bruers, Stijn (Environmental ethics, 2022)
Is animal farming permissible when animals would have a positive welfare? The happy animal farming problem represent the paradigmatic problem in population ethics, because its simple structure introduces the most important complications of population ethics. Three new population ethical theories that avoid the counter-intuitive repugnant and sadistic conclusions are discussed and applied to the animal farming problem. Breeding farm animals would not be permissible according to these theories, except under some rather unrealistic conditions, such as those farm animals being so happy that they themselves would prefer a continuation of animal farming. Given the fact that many people believe that most farm animals are not so happy and the fact that one can formulate reasonable population ethical theories that condemn happy animal farming, it can be concluded that it is better to avoid animal farming and the consumption of animal products in general.